Nutrition cycles in sessile oak (Quercus petraea Liebl.), Norway spruce (Picea abies L.Karst) and European beech (Fagus sylvatica L.) stands from Central Romania - Raluca-Elena Enescu; Alexandru Liviu Ciuvăț; Lucian Dincă; Carmen Iacoban; Elena Deleanu; Cristian Anghelus (Open Journal of Environmental Biology - Peertechz Publications, 2022)
In Romania, the sessile oak is the widest spread species of all native oak species, forming a lower story of vegetation. The European beech and Norway spruce cover 50% of the Romanian forest area. The purpose of this study was to analyze the variability of the leaf nutrients, as well as of the soil nutrients, for sessile oak, Norway spruce and European beech stands situated under different site conditions. The studied sites are located in the southern part of the Carpathian Mountains at altitudes varying from 600 m to 1300 m. Leaves samples were collected from twenty sessile oak trees, in three moments during the growing season. The same eight elements in total form were determined for soil and leave too: N, P, K, Ca, Mg, Fe, Cu and Zn. Leaves samples for beech and spruce were collected in the II Level Intensive Monitoring Grid of the ICP Forests Programme. The paper focuses on the seasonal concentration variation of eight macro elements in leaves and the correlations between the concentration of the macro elements in soil and litter. In addition, the study highlighted the degree of influence exerted by some soil properties on the foliar concentration of nutrients (through multiple regressions). The obtained results show different mobility of the elements and a greater variability was noticed in the case of certain elements. The same three soil properties were noticed to influence the foliar nitrogen concentration.